STUDY OF EFFECTS OF PH AND INHIBITORâS CONCENTRATION TOWARD DL-METHIONINE AND L-TRYPTOPHANâS ACTIVITIES AS CORROSION INHIBITORS FOR CARBON STEEL - Claudia
Steel is one of iron’s alloys that has various uses in various aspects of life. But, steel is vulnerable to corrosion because of its interaction with the environment, such as acids, air, and electrolyte solutions. Many kinds of compounds that have been used to inhibit steel’s corrosion, but most of them are not environmentally friendly. Thus, environmentally friendly corrosion inhibitors become crucial to be learned. In this research, amino acids DL- Methionine (DL-Met) and L-Tryptophan (L-Trp) are used as organic compounds for carbon steel electrode’s corrosion inhibition. Activities of corrosion inhibition by those amino acids were being tested in various electrolyte solution’s conditions, such as 0.05 M HCl (acidic), 3% NaCl (neutral), and 0.05 M NH4OH (basic). The methods that were being used for this research are Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization (PDP). From EIS data, the inhibition efficiency value (?) for DL-Met reaches 40,06% at 525 ppm and for L-Trp reaches 44,13% at 25 ppm in HCl. At the concentration below 125 ppm (DL-Met) and 6 ppm (L-Trp), the amino acids are still not effective as corrosion inhibitors. Both DL-Met and L-Trp also don’t have inhibition properties in neutral and basic condition. Based on PDP data, DL-Met and L-Trp are mixed type inhibitors because they inhibit both cathodic (bc) and anodic (ba) reactions in the system. Values of ? for DL-Met is 53,64% at 525 ppm and for L-Trp is 50,41% at 25 ppm in HCl. The values of corrosion current (icorr) are decreased from 0,8551 mA to 0,3486 mA (DL-Met) and from 0,9368 mA to 0,4278 mA (L-Trp). In the same condition, corrosion rate values are reduced from 10 mm/Y to 4,077 mm/Y (DL-Met) and from 10,95 mm/Y to 5,003 mm/Y (L-Trp).